Meta-Analysis of Think-Talk-Write (TTW) Learning Model to Improve Student's Mathematics Problem Solving Ability - Robby Jeremia Praja Simarmata; Nurhasanah Siregar (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2022)
The purpose of this study was to determine the effect size of the influence of Think-Talk-Write learning in improving students' mathematical problem-solving abilities by describing: (1) Overall Effect size, (2) Effect size Based on Educational Level, (3) Effect size Based on Material What is taught, (4) Effect size Based on Learning Media/ LKPD. The population is sinta-accredited national journals that are available via the internet. In taking the sample used, the purposive sampling technique. The data analysis technique is tabulation and calculating the effect size using Cohen's d formula. Conclusions: (1) Overall, the seven journal articles obtained an effect size of 0.81, which indicates that the think talk writing learning model has a moderate effect in improving students' mathematical problem-solving abilities, (2) Think talk writing learning is more widely applied at the education level. SMP/MTs level by obtaining an effect size value of 0.83, while the effect size value for SMA/SMK level education is 0.76, (3) The area of ??the circle is the material that has the most significant effect size effect, which is 1.65 high effect category, ( 4) An effective learning media in the application of think talk write learning, one of which is the Prezi application Keywords: A meta-analysis, think talk, learning, math problem-solving skills.